(untitled) (Journal of the College of Basic Education, 2023)
In this research, a ZnO film was prepared by thermochemical decomposition method, with a thickness of (300 nm) on a glass base, where the optical and electrical properties were studied.It was found through the results of X-ray diffraction (X-Ray) that the films have a polycrystalline structure, and the relationship of both the absorbance and the transmittance was studied as a function of the photon energy for the ZnO films, and the allowed energy gap for the direct transmission allowed for the films was calculated and it was (3.14eV), and the absorption coefficient was studied as a function of energy photonSpeke’s results showed that ZnO films have n-type donor conductivity.